FORMATION OF VISUAL AND INFORMATION CULTURE OF PRE-SERVICE MATHEMATICS AND COMPUTER SCIENCE TEACHERS: A COGNITIVE CRITERION - Drushlyak, Marina (Physical and Mathematical Education, 2021)
Formulation of the problem. With the growing educational content volume and increasing the visualization role in the educational process, the ability to perceive, analyze, compare, interpret, produce using information technology, structure, integrate, evaluate visually presented educational material increases the teachers’ competitiveness in the labor market. In other words, teachers with formatted visual and information culture are needed.Materials and methods. The study was based on scientific research of national and foreign scientists studying the training of pre-service mathematics and computer science teachers. To achieve this goal, the methods of the theoretical level of scientific knowledge were used: analysis of scientific literature, synthesis, formalization of scientific sources, description, comparison, and statistical methods: Pearson's test; Student's t-test.Results. Cognitive criterion is characterized by the presence of subject, methodological, psychological and technological knowledge on the visualization and digitalization of education. Indicators of the cognitive criterion are: the degree of awareness of the availability of computer visualization tools and the possibility of their use in the educational process; availability of a system of knowledge in the field of information visualization and basics of cognitive and visual technologies, the classification of special software, computer visualization means, the possibility of using computer visualization taking into account the educational purpose, selected forms and methods of teaching, about psychological and age features of perception of educational content, about structuring of educational content; level of development of visual thinking. Statistical calculations confirmed that the experimental groups EG1, EG2 and the control group KG have statistically different averages at a significance level of 0.05.Conclusions It would be impossible to ensure the positive dynamics of changes in the indicators of the cognitive criterion of formation of visual and information culture within the framework of the traditional approach to the professional training of pre-service mathematics and computer science teachers. This testifies to the effectiveness of the author's pedagogical system of formation of visual and information culture of pre-service mathematics and computer science teachers, which is realized by correcting the content of training pre-service teachers (introduction of special courses, deepening the content of professional disciplines), active involvement of students in research works on cognitive visualization problems, participation in student scientific conferences), use of non-formal education (participation in trainings, master classes, webinars).
Keywords: visual and information culture; pre-service mathematics and computer science teachers; cognitive criterion; knowledge system; visual thinking